Perilaku Makan dan Kejadian Gizi Lebih pada Mahasiswa STIKes Mitra Keluarga - Noerfitri Noerfitri; Pravangasta Aneliana Aulia (FORIKES, 2022)
Overnutrition experienced by adolescents can be caused by several factors, including eating behavior. This study aims to determine the relationship between eating behavior and the incidence of overnutrition in adolescents at STIKes Mitra Keluarga. This type of research was quantitative with a cross-sectional design. The independent variables were eating behavior which consists of 3 aspects (emotional eating, restraint eating and external eating) and the dependent variable was nutritional status. The research subjects studied were 210 students of STIKes Mitra Keluarga with an age range of 17 to 20 years. The data that had been obtained were analyzed by independent sample t-test. The results showed that 39.5% of students had more nutritional status and there was a relationship between eating restraint eating behavior and the incidence of overnutrition (p-value = 0.001) but there was no relationship between eating behavior emotional eating and external eating with the incidence of overnutrition, respectively. -with p-values of 0.497 and 0.143, respectively.Keywords: eating behavior; overnutrition; teenager ABSTRAK Gizi lebih yang dialami remaja dapat disebabkan oleh beberapa faktor di antaranya adalah perilaku makan. Penelitian ini bertujuan untuk mengetahui hubungan antara perilaku makan dengan kejadian gizi lebih pada remaja di STIKes Mitra Keluarga. Jenis penelitian ini adalah kuantitatif dengan desain cross-sectional. Variabel independen adalah perilaku makan yang terdiri dari 3 aspek (emotional eating, restraint eating dan external eating) dan variabel dependen yaitu status gizi. Subjek penelitian yang diteliti adalah 210 mahasiswa STIKes Mitra Keluarga dengan rentang usia 17 sampai 20 tahun. Data yang telah diperoleh dianalisis dengan independent sample t-test. Hasil penelitian menunjukkan bahwa 39,5% mahasiswa memiliki status gizi lebih dan terdapat hubungan antara perilaku makan restraint eating dengan kejadian gizi lebih (p-value = 0,001) namun tidak ada hubungan antara perilaku makan emotional eating dan external eating dengan kejadian gizi lebih, masing-masing dengan p-value 0,497 dan 0,143.Kata kunci: perilaku makan; gizi lebih; remaja